Indonesian Government’s Motive and Literary Taste: A Perspective on the Translation Funding Program (TFP) - M. Yuseano Kardiansyah; Aprinus Salam; Nur Saktiningrum (Ahmad Dahlan Journal of English Studies, 2022)
The translation Funding Program (TFP) was initiated concerning the Indonesian government agenda to be the guest of honor at the Frankfurt Book Fair (FBF) 2015. As a result, it produced many Indonesian-English literary translations, particularly the two from Yogyakarta. By applying the Bourdieusian approach to cultural production, this study is arranged to unravel the government’s motive and literary taste behind the execution of that program, especially through the production of two literary works, “Pilgrimage in the Land of Java” and “Jatisaba.” This study is directed to figure out the importance of Indonesian-English translation for Indonesian literature and the criteria of literary works to be involved in such a government program. Therefore, the government’s motive and literary taste behind the TFP can be elaborated further. There are two primary techniques for the data collection in this research; 1. Digital library research is utilized to access relevant information about TFP, and 2. Interview the writers to get information about their experience participating in TFP. All collected data are synchronized in the analysis to explain the binding knot among the literary translation production, TFP, and FBF. As a result,the study reveals that there were some motives behind the production of literary translation through the TFP. Those motives were also related to the literary taste influenced by international demand.